Enhancing Hydrogen Storage Properties of Metal Hybrides Enhancement by Mechanical Deformations - Huot, Jacques; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book shows how severe plastic deformation techniques could be used to enhance the hydrogen storage properties of metal hybrides. The mechanochemical techniques of ball-milling (BM), Cold Rolling (CR), Equal Chanel Angular Pressing (ECAP) and High Pressure Torsion (HPT) are covered. Each technique is described and critically assessed with respect to its usefulness to process metal hybrides at an industrial scale.
Keywords: Metals; Microtechnology; Microelectromechanical systems; Energy storage; Metals and Alloys; Microsystems and MEMS; Mechanical and Thermal Energy Storage